Addressing Literacy Needs of Struggling Spanish-Speaking First Graders: First-Year Results From a National Randomized Controlled Trial of Descubriendo la Lectura - Trisha H. Borman; Geoffrey D. Borman; Scott Houghton; So Jung Park; Bo Zhu; Alejandra Martin; Sidney Wilkinson-Flicker (SAGE Publishing, 2019)
Given the growing number of Latino English learners and the lack of evidence-based educational opportunities they are provided, we investigated the impact of one potentially effective literacy intervention that targets struggling first-grade Spanish-speaking students: Descubriendo La Lectura (DLL). DLL provides first-grade Spanish-speaking students one-on-one literacy instruction in their native language and is implemented at an individualized pace for approximately 12 to 20 weeks by trained bilingual teachers. Using a multisite, multicohort, student-level randomized controlled trial, we examined the impact of DLL on both Spanish and English literacy skills. In this article, we report findings from the first of three cohorts of students to participate in the study. Analyses of outcomes indicate that treated students outperformed control students on all 11 Spanish literacy assessments with statistically significant effect sizes ranging from 0.34 to 1.06. Analyses of outcomes on four English literacy assessments yielded positive effect sizes, though none were statistically significant.